25. Intraoperative neurophysiology in pediatric neurosurgery. Issue 9 (September 2016) - Sala, Francesco; Tramontano, Vincenzo; Coppola, Angela; Babini, Micol; Meneghelli, Pietro
Abstract : Intraoperative neurophysiological monitoring (IONM) techniques commonly used in adults should be tailored to pediatric patients. Below the age of 5–6 years, the classical Penfield's method for cortical mapping often fails to elicit a muscle response due to the immaturity of the motor cortex and the corticospinal tract, while the motor evoked potential (MEP) short-train technique seems more effective. The use of awake surgery in children remains anecdotal and whenever cognitive function need to be investigated, a two-stage surgical approach with the use of subdural grids represents a valid alternative. In brainstem surgery, mapping techniques are valuable in selecting safe entry zones to the dorsal brainstem and during the removal of fourth ventricle tumors infiltrating the brainstem. Combination of direct mapping and subcontinuous monitoring of the corticobulbar MEPs for lower motor cranial nerves minimizes the risk of compromising swallowing and coughing reflexes. In spinal cord surgery, is difficult to record the D-wave in children younger than two years, but its critical role in predicting long-term motor outcome is confirmed in pediatric spinal cord tumors. During surgery of the conus-cauda for spinal dysraphisms, mapping techniques are essential to identify and spare functional neural tissue and, vice versa, to cut non functional structures that may contribute to cord tethering.